2011
DOI: 10.1111/j.1943-278x.2011.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Sadness, Suicide, and Their Association with Video Game and Internet Overuse among Teens: Results from the Youth Risk Behavior Survey 2007 and 2009

Abstract: We investigated the association between excessive video game/Internet use and teen suicidality. Data were obtained from the 2007 and 2009 Youth Risk Behavior Survey (YRBS), a high school-based, nationally representative survey (N = 14,041 and N = 16,410, respectively). Teens who reported 5 hours or more of video games/Internet daily use, in the 2009 YRBS, had a significantly higher risk for sadness (adjusted and weighted odds ratio, 95% confidence interval = 2.1, 1.7-2.5), suicidal ideation (1.7, 1.3-2.1), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 31 publications
11
98
1
8
Order By: Relevance
“…It could be these youths suffer from depression and therefore play pathologically to escape negative emotions, or it could be pathological play has led to depression. Other research has found that young people who report excessive video game play (five hours or more per day) are more likely to report pervasive feelings of sadness or hopelessness, stopping participating in usual activities, and suicidal ideation and suicidal plans (Messias et al, 2011). Correlations have been found for video game addiction and depression, poor academic achievement, heavy drinking, and conduct problems (Brunborg, Mentzoni, & Frøyland, 2014).…”
Section: Gambling and Video Game Playing 106mentioning
confidence: 85%
See 2 more Smart Citations
“…It could be these youths suffer from depression and therefore play pathologically to escape negative emotions, or it could be pathological play has led to depression. Other research has found that young people who report excessive video game play (five hours or more per day) are more likely to report pervasive feelings of sadness or hopelessness, stopping participating in usual activities, and suicidal ideation and suicidal plans (Messias et al, 2011). Correlations have been found for video game addiction and depression, poor academic achievement, heavy drinking, and conduct problems (Brunborg, Mentzoni, & Frøyland, 2014).…”
Section: Gambling and Video Game Playing 106mentioning
confidence: 85%
“…There is ample research indicating significant correlations between gambling, problem gambling, and depression (Bonnaire, Bungener, & Varescon, 2009;Gupta & Derevensky, 1998a;Kim, Grant, Eckert, Faris, & Hartman, 2006;Martin, Usdan, Cremeens, & Vail-Smith, 2014;McCormick, Russo, Ramirez, & Taber, 1984;Potenza et al, 2001). Adolescents with gambling problems report higher rates of depression, alcohol abuse, anxiety, and are at heightened risk for both reported suicide ideation and attempts (Desai, Maciejewski, Pantalon, & Potenza, 2005;Kaminer, Burleson, & Jadamec, 2002;Molde, Pallesen, Bartone, Hystad, & Johnsen, 2009;Moodie & Finnigan, 2006a; While in its infancy, the research on gaming and depression supports a positive relationship between problematic gaming (as measured by time spent playing or the Game Addiction Scale (Lemmens et al, 2011)), and depression (Desai, Krishnan-Sarin, Cavallo, Gambling and Video Game Playing 26 & Potenza, 2010;Lemmens et al, 2011;Mentzoni et al, 2011;Messias, Castro, Saini, Usman, & Peeples, 2011). Problem video game players have been found to have higher levels of anxiety and depression and lower life satisfaction compared with both non-gamers and non-problem gamers and are more likely to report suicidal ideation and suicidal plans than those who do not play video games (Desai et al, 2010;Mentzoni et al, 2011;Messias et al, 2011).…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…5 per day (Messias et al, 2011), and "dependent" video-gaming as more than 10 hours per week (Huang, 2006). However, as Griffiths (2010) has shown using case studies, the time spent engaged in gaming is not necessarily an indicator of problematic play and that context is critical when using time as criterion for addictive gaming.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Research indicates that the average weekly screen-time of youth has increased by 43 hours in the last few years, suggesting that adolescents now spend approximately 11 hours a day interacting with a digital media device (O'Loughlin, Lambert, Gauvin, Kestens, & Daniel, 2008;Rideout, Foehr, & Roberts, 2010;Rideout, Pai, & Saphir, 2015). Some research has showcased the social and educational benefits that come from teenager technology use (GLSEN, CiPHR, & CCRC, 2013;Hickerson & Mowen, 2012;Pew Research Center, 2015), however, more numerous studies have attributed negative and deteriorating mental health to the increasingly ubiquitous digital media consumption amongst adolescents (Martin, 2011;Messias, Castro, Saini, Usman, & Peeples, 2011;Rosen, Whaling, Rab, Carrier, & Cheever, 2013). Despite these initial and, in some cases, mixed findings, current understanding of how access to, and interaction with, technology impacts on our youth's development is impoverished.…”
Section: Introductionmentioning
confidence: 99%